Compliance of the Nurse for Fall Risk Assessment as a Procedure of Patient Safety: A Systematic Review - Nadia, P; Yulianty Permanasari, V (KnE Life Sciences, 2018)
Fall is an incident that is often reported in hospitals. Fall can result in a loss to the patient. Fall risk assessment is an operational standard procedure that becomes a part of the performance and behaviour of the nurses. The aim of this study is to find out the level of compliance of the nurses in assessing the risk of fall in hospitalized patients. This study uses systematic review based on the Prisma Protocol. A search was conducted on electronic databases ProQuest, Scopus, and Google Scholar using relevant keywords. The relevant studies were further selected using inclusion and exclusion criteria. Twelve studies were included in this review. Five studies were conducted in wards, one study in emergency room, and six studies did not specifically mention the place. All studies show that nurses are already quite obedient in doing the standard operational procedure but there are still many nurses who do not do the fall risk assessment. The compliance of the nurses are influenced by the assessment instrument Morse scale, socialization of the operational standard procedure by the supervisor, level of education, age, work experience, and team work. As conclusion, the compliance of the nurses in assessing the risk of fall in patients is getting better. The most important factor is the availability of assessment instrument. Keywords: fall, fall risk assessment, nurses’ compliance, patient safety, Morse scale